2011
DOI: 10.1038/ja.2011.9
|View full text |Cite
|
Sign up to set email alerts
|

A new anti-MRSA antibiotic complex, WAP-8294A II. Structure characterization of minor components by ESI LCMS and MS/MS

Abstract: The anti-MRSA antibiotic, WAP-8294A, was isolated from the fermentation broth of Lysobacter sp. The major component,and 2 mol of L-Ser, D-Orn and D-3-hydroxy-7-Me-octanoic acid. The structure of the WAP-8294A2 was mainly determined as a cyclic depsipeptide by 2D NMR experiments. However, it was difficult to use the NMR experiment to determine the minor components, A1, A4 and Ax13, isolated in small amounts. In the present study, ESI MS/MS was applied to the structure elucidation of these minor components. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 24 publications
2
26
0
Order By: Relevance
“…The results suggested that the WAP-8492A biosynthetic pathway likely recruits an ACL from other pathways. This type of in trans ACL generally exhibits a broad specificity and is functionally redundant (2), which is consistent with the fact that all WAP-8492A compounds have the same amino acid composition but vary in the length of the fatty acid side chain (16,(22)(23)(24).…”
Section: Resultssupporting
confidence: 76%
See 3 more Smart Citations
“…The results suggested that the WAP-8492A biosynthetic pathway likely recruits an ACL from other pathways. This type of in trans ACL generally exhibits a broad specificity and is functionally redundant (2), which is consistent with the fact that all WAP-8492A compounds have the same amino acid composition but vary in the length of the fatty acid side chain (16,(22)(23)(24).…”
Section: Resultssupporting
confidence: 76%
“…13 C NMR data are summarized in Table 1 ( 1 H and 13 C NMR spectra and selected HSQC correlations are provided in the supplemental material). A comparison of these data to those in the literature readily revealed that this compound is WAP-8294A2, a cyclic lipodepsipeptide originally isolated from L. staphylocidin (16,(22)(23)(24). WAP-8294A2 consists of 12 amino acid residues and a fatty acid side chain (3-hydroxy-7-methyloctanoic acid) (Fig.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…Liquid chromatography coupled with electrospray ionization tandem mass spectrometry (LC/ESI-MS/MS) has become the main method for analyzing proteins and peptides [Kato et al, 2011]. It is also used to analyze CLPs, such as fengycin [Bie et al, 2009;De Faria et al, 2011;Wang et al, 2004], surfactin [Cho et al, 2003a;Lee et al, 2007;Pecci et al, 2010;Wang et al, 2010] and iturin [Caldeira et al, 2011;Cho et al, 2003b].…”
Section: Introductionmentioning
confidence: 99%